2022
DOI: 10.1039/d2md00199c
|View full text |Cite
|
Sign up to set email alerts
|

A ‘click’ chemistry approach to novel entinostat (MS-275) based class I histone deacetylase proteolysis targeting chimeras

Abstract: Click chemistry was utilised to prepare a library of PROTACs based on entinostat a class I histone deacetylase (HDAC) inhibitor in clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…A real feat of the PROTAC technology would to be selectively degrade HDAC1 over HDAC2 or vice versa given the high amino acid sequence similarity between HDAC1 and HDAC2. With PROTACs 4 and 5 the dose response curves for HDAC1 and HDAC2 degradation mirror one another, however we have consistently observed greater HDAC1 degradation levels over HDAC2 degradation, 54,58,59 at least suggesting this may be viable. Regards targeting HDAC1 and HDAC2 for degradation, there are PROTACs reported that degrade HDAC1 and HDAC2, however not with complete selectivity and work still needs to be done to fine tune HDAC1 and HDAC2 degradation over the degradation of other HDAC isoforms.…”
Section: Protacs Targeting Class I Hdacsmentioning
confidence: 55%
See 1 more Smart Citation
“…A real feat of the PROTAC technology would to be selectively degrade HDAC1 over HDAC2 or vice versa given the high amino acid sequence similarity between HDAC1 and HDAC2. With PROTACs 4 and 5 the dose response curves for HDAC1 and HDAC2 degradation mirror one another, however we have consistently observed greater HDAC1 degradation levels over HDAC2 degradation, 54,58,59 at least suggesting this may be viable. Regards targeting HDAC1 and HDAC2 for degradation, there are PROTACs reported that degrade HDAC1 and HDAC2, however not with complete selectivity and work still needs to be done to fine tune HDAC1 and HDAC2 degradation over the degradation of other HDAC isoforms.…”
Section: Protacs Targeting Class I Hdacsmentioning
confidence: 55%
“…In a separate study, we investigated utilising the class I HDAC inhibitor entinsotat as inspiration for PROTAC 6 . 59 PROTAC 6 encompassing the triazole and carbamate moiety was also a degrader of HDAC1, HDAC2 and HDAC3 in HCT116 cells, but was reduced in degradation potency (HDAC1 DC 50 = 2.8 μM) compared to 4 and 5 . PROTAC 6 also exhibited a similar hook effect for HDAC3 although at higher concentrations, above 2.5 μM.…”
Section: Protacs Targeting Hdac1 and Hdac2mentioning
confidence: 92%
“…At the present, more than 10 PROTAC degraders have entered clinical Phase I‐II trials with ARV‐471 and ARV‐110 from Arvinas, Inc as the most advanced ones for the treatment of recurrent breast cancer and prostate cancer, respectively 46–49 . However, PROTAC still faces many challenges 50–65 . A typical PROTAC degrader consists of three components: the target‐binding small molecule ligand (protein of interest, POI), the E3 ligase ligand and the appropriate linker that connects the two components (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“… 46 , 47 , 48 , 49 However, PROTAC still faces many challenges. 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 A typical PROTAC degrader consists of three components: the target‐binding small molecule ligand (protein of interest, POI), the E3 ligase ligand and the appropriate linker that connects the two components (Figure 1 ). 50 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 E3 ligases and the corresponding ligands are important as the driving force of protein degradation.…”
Section: Introductionmentioning
confidence: 99%
“…While click chemistry has been employed as a synthetic strategy for the generation of various degraders, the impact of the embedded triazole has been largely unexplored. 15,26,27 Examining the role of this rigid moiety is critical given the ability of linkers to engage in intermolecular interactions within ternary complexes that impact degradation potency. 28 In this study, variation of the rigid triazole position across the flexible alkyl linker resulted in differences in CDK9 degradation, overall in vitro activity, kinetic solubility (KS), and lipophilicity.…”
mentioning
confidence: 99%